PARENTAL INTERPERSONAL SKILLS AND ADOLESCENT ATTITUDES TOWARD EARLY MARRIAGE - Wardani, Diadjeng Setya; Anika Pratiwi, Sindy; Putri, Rismaina; Jannah, Miftahul; Diana Fransisca, Ratna; Retno Hastuti, Nur Aini (Universitas Airlangga, 2025)
Introduction: Early marriage is one of the cases with the highest incidence in Indonesia involving teenagers under the age of 19 years. Based on religious court records, 1711 cases were recorded, or an increase of 35% compared to the previous year. Many factors cause this, namely from oneself and environmental factors. Adequate guidance in educating children is an important role that can be carried out effectively by parents. Aims: This research aims to determine the influence of interpersonal skills and parental knowledge on teenagers' attitudes toward early marriage. Method: This research method is descriptive analytical research with a cross-sectional approach. This research was attended by 60 respondents, consisting of 30 teenage respondents and 30 respondents who were parents of teenagers. Data collection was carried out by filling out a questionnaire which was analyzed using the Chi-square test. Results: The results of the study show that parents' interpersonal skills in responding to early marriage are in the sufficient category, there is an influence of parents' interpersonal skills in responding to early marriage on teenagers' attitudes (p=0.001), there is an influence of parents' latest education on parents' level of knowledge about early-age marriage. (p=0.001). Conclusion: The research conclusion shows that there is an influence of interpersonal skills and parental knowledge on teenagers' attitudes in responding to early marriage, and the parents' latest education has an influence in responding to early marriage.